Resistencia al desgate abrasivo de recubrimiento con aleacion Estelita e Inconel 600 - Castillo, M.=700 1 Villa, G.; Vite, M.; Villegas, P.; Hernandez, L.
(En, Es)
ilus., 12 ref.
Keywords: MAQUINARIA DE CULTIVO; DESGASTE; ALEACIONES; COBALTO; CROMO; NIQUEL; MEXICO; DESGASTE ABRASIVO; RECUBRIMIENTO CON ALEACION; ESTELITA; INCONEL 600